Derecho administrativo general : apuntes y reflexiones contemporáneas para una pedagogía prospectiva del derecho - De Los Ríos Castiblanco, Juan Carlos (Corporación Universitaria Americana, 2022)
The book Administrative Law, is an academic support for the university and research community, which was developed with the objective of strengthening knowledge, knowing in good ink common pedagogical strategies in the teaching of public law, identifying the topics that present learning difficulties and developing optional methods of assistance to the teaching process; it was prepared by teachers and lawyers specialized in the area of administrative law and participants of the research group DehJüs and Law & Science.